2020
DOI: 10.1177/1741143220940324
|View full text |Cite
|
Sign up to set email alerts
|

Leadership emergence and development: Organizations shaping leading in early childhood education

Abstract: Early childhood education (ECE) effects positive outcomes for children, but outcomes depend upon the quality of the program with which children engage. Program quality is positively influenced by effective leadership; yet we do not fully understand how effective leadership emerges and develops within ECE sites. This lack of knowledge potentially compromises the development of effective leadership and, subsequently, a child’s right to high-quality ECE. This paper, therefore, contributes to the field of research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 40 publications
(71 reference statements)
2
37
0
Order By: Relevance
“…Similarly to DCA reports, Golebiowska et al (2018) state that overseas-born educators tend to stay in their jobs longer than their Australian-born counterparts. (Gibbs, 2020;Gide, 2017), the wellbeing of the educators (Cumming et al, 2021;Cumming & Wong, 2018), and workforce issues (Irvine et al, 2016;.…”
Section: Cald Workforce In the Context Of Australian Ecementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to DCA reports, Golebiowska et al (2018) state that overseas-born educators tend to stay in their jobs longer than their Australian-born counterparts. (Gibbs, 2020;Gide, 2017), the wellbeing of the educators (Cumming et al, 2021;Cumming & Wong, 2018), and workforce issues (Irvine et al, 2016;.…”
Section: Cald Workforce In the Context Of Australian Ecementioning
confidence: 99%
“…Having a CALD workforce may also be beneficial for CALD families. The number of CALD children and families using ECE settings is increasing every year (Productivity Commission Reports, 2013-2020. ECE settings are assessed against seven NQS.…”
Section: The Potential Benefits Of a Cald Ece Workforce For Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors included the feel of the setting and educators’ view of children as capable. A study by Gibbs (2020a) identified particular leadership practices that can contribute toward high quality. Practices included many educators engaging in the act of leading, not just those in leadership positions.…”
Section: Educator Research Participation For High-quality Early Childhood Educationmentioning
confidence: 99%
“…Leadership is, however, enacted within Australian ECEC sites in a milieu of people, policy and practice (Alchin et al, 2019), and the profession remains hampered by multiple challenges that may make the proposition of positional leadership unpalatable. Challenges include complex workforce issues, inadequate preparation for positional leadership roles, inadequate understandings of leadership theory and conceptualisations and few opportunities for professional development for emerging leaders (Alchin, 2019;Gibbs, 2020;Waniganayake et al, 2017). These persistent challenges jeopardise the growth of effective leadership and the development of a sustainable leadership pipeline for the early childhood education profession.…”
Section: Introductionmentioning
confidence: 99%